Pengaruh Daya Tarik Wisata, Media Sosial Dan Nilai Terhadap Minat Berkunjung Ke Desa Wisata Hutan Mangrove Kulon Progo Yogyakarta - Mony, Ruslia; Prasetyo, Heri (CV. Kurnia Grup, 2024)
This research aims to determine the partial and simultaneous influence of tourist attractions, social media and values on tourists' interest in visiting the Kulon Progo Mangrove Forest Tourism Village. This research uses a quantitative type of research. The population in this study was the penjung mangrove forest tourism village of Kulon Progo. The sample in the study was 249 respondents. The sampling technique was taken using purposive sampling, a sample determination method based on the researcher's considerations which was then processed using SPSS. The data collection technique in this research uses a questionnaire. The instrument testing technique in this research uses validity and reliability. And the data analysis technique in this research uses classical assumptions, multiple linear regression, coefficient of determination and hypothesis testing. The results of this research are as follows. Partially, tourist attraction has a significant effect on tourists' interest in visiting the Kulon Progo tourist village, marked by a t-value of 4.984 which is greater than the t-table of 1.97.